Response of osteoblast‐like MC3T3‐E1 cells on bioactive titanium fabricated by a chemical treatment process using a calcium‐phosphate slurry. Issue 11 (17th December 2013) - Ohtsu, Naofumi; Hirano, Mitsuhiro; Arai, Hirofumi
Abstract We recently developed a chemical treatment process using a calcium‐phosphate slurry for fabricating new layers consisting of hydroxyapatite and titanium dioxide (TiO2) on titanium (Ti) substrate. In this study, the response of osteoblast‐like MC3T3‐E1 cells on Ti substrate treated with a calcium‐phosphate slurry was investigated to elucidate its behavior in a biological environment. The cellular adhesiveness and proliferation capacity did not differ significantly between the treated and untreated Ti substrates, suggesting that the slurry treatment did not cause cytotoxicity. The slurry treatment did not affect the increase in alkaline phosphatase activity after the induction of cell differentiation, whereas it was found to be significantly advantageous for the calcification behavior on the slurry‐treated Ti substrate. In consequence, the hard‐tissue compatibility of Ti is expected to be improved by the chemical treatment process using a calcium‐phosphate slurry. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3838–3845, 2014.